2019
DOI: 10.1101/607721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-marked chromatin and transcription factor co-binding shape the pioneering activity of Foxa2

Abstract: Pioneer transcription factors (PTF) can recognize their binding sites on nucleosomal DNA and trigger chromatin opening for recruitment of other non-pioneer transcription factors. However, critical properties of PTFs are still poorly understood, such as how these transcription factors selectively recognize cell type-specific binding sites and under which conditions can they can initiate chromatin remodelling. Here we show that early endoderm binding sites of the paradigm PTF Foxa2 are epigenetically primed by l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 62 publications
6
13
0
Order By: Relevance
“…Higher active chromatin signals were also observed at the proximal (Fig. 5f, ATAC and H3K4me3) and distal ( Recent studies demonstrate that FOXA2 triggers chromatin opening on a subset of its potential binding sites during endoderm differentiation 37 . In the present study, we found that FOXA2 target sites acquiring 5hmC during pancreatic differentiation correlate with high levels of active chromatin modifications (Fig.…”
Section: Tet1 Binding Sites Are Distinct In Pancreatic Progenitors Tmentioning
confidence: 80%
See 1 more Smart Citation
“…Higher active chromatin signals were also observed at the proximal (Fig. 5f, ATAC and H3K4me3) and distal ( Recent studies demonstrate that FOXA2 triggers chromatin opening on a subset of its potential binding sites during endoderm differentiation 37 . In the present study, we found that FOXA2 target sites acquiring 5hmC during pancreatic differentiation correlate with high levels of active chromatin modifications (Fig.…”
Section: Tet1 Binding Sites Are Distinct In Pancreatic Progenitors Tmentioning
confidence: 80%
“…Several studies suggest that TET can be directly recruited by pioneer TFs, such as FOXA1 and PU.1, to lineage-specific enhancers to facilitate local demethylation and gene induction 46,47 . However, a recent study found that chromatin opening requires cooperative binding of FOXA2 and additional TFs, such as GATA4, during endoderm differentiation 37 . This suggests complex cross-talk between pioneer TFs and chromatin remodelers in endodermal lineage specification.…”
Section: Discussionmentioning
confidence: 98%
“…Among endoderm factor motif combinations, we found that particular orientations of FoxA2 and Gata4 (Figure 5e) and of Sox17 and Gata4 (Figure 5f) promoted more differential accessibility that again were consistent with the effects seen from endoderm DNase-seq ( Supplementary Figure 16; see Supplementary Methods for details). Previous studies have implicated Gata family members as pioneering transcription factors 1 , including evidence that Gata4 interacts with FoxA2 to drive accessibility changes during endoderm differentiation 30 .…”
Section: Exploration Of Ordering Of Pioneer Transcription Factors mentioning
confidence: 99%
“…Previous work has indicated specific transcription factor motifs and logic governing chromatin accessibility [28][29][30] , but such effects are difficult to disentangle in a native genomic context, where motifs are not independent of non-local sequence effects. Recent approaches have extended MPRAs to measure nucleosome occupancy via bisulfite treatment 31 or MNase-seq 32 in yeast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation